Implementasi Clinical Pathway dengan Analisa Penggunaan Antibiotika, Pasien Anak dengan Demam Tifoid Rawat Inap - Jonnefi Jonnefi (Jurnal Health Sains, 2023)
Clinical Pathway (CP) is an important part of the documents and tools to realize good clinical governance in hospitals. In Indonesia, this document is also one of the requirements that must be met in the Hospital Accreditation Standard version of the Hospital Accreditation Commission (KARS). The aim of this study was to determine the effectiveness of implementing CP in pediatric patients with typhoid fever on clinical outcomes, length of stay, use of antibiotics at Permata Bekasi Hospital. Providing information and scientific data regarding the implementation of CP on clinical outcomes and can be used as a reference material in making programs and regulation of antibiotics used for pediatric patients with typhoid fever in a rational manner. The research used is a quantitative method with a pre and post approach after the implementation of CP using secondary data, namely medical records of patients with typhoid fever hospitalized at Permata Bekasi Hospital retrospectively. The age group before CP was the most aged 5 - <10 years (29.8%), as well as the group after CP the most aged 5 - <10 years (34.7%), it can be concluded that the age range was diagnosed with typhoid fever more than the age of the other patients. The effectiveness of CP implementation after CP can reduce the average length of stay according to CP recommendations compared to before CP implementation.